2003
DOI: 10.1039/b2rp90036j
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Irish Students' Attitudes to Chemistry: The Promotion of Chemistry in Schools Project

Abstract: Ireland's student participation in the sciences at Leaving Certificate (LC) level (17 years) has fallen considerably in the last fifteen years. We evaluate the opinions and attitudes of students at Junior Certificate (15 years) to science, prior to LC subject choice, as part of an intervention strategy to promote chemistry. This article is concerned with the reasons given by a group of third year students for their like or dislike of science and their reasons for choosing to study chemistry in the future. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The main reason that has been put forward for this decline is the lack of interest shown by students in the physical Sciences. Research conducted by Regan and Childs (2003), which consisted of a survey of 88 second level students, showed that 71.6% of students considered Biology to be the most interesting Science, the Physical Sciences (Physics and Chemistry) showed quite a different picture. The least popular Science is physics with 62.4% of the students considering it the least interesting of the Sciences and only 8.2%…”
Section: Attitudes Towards Sciencementioning
confidence: 99%
“…The main reason that has been put forward for this decline is the lack of interest shown by students in the physical Sciences. Research conducted by Regan and Childs (2003), which consisted of a survey of 88 second level students, showed that 71.6% of students considered Biology to be the most interesting Science, the Physical Sciences (Physics and Chemistry) showed quite a different picture. The least popular Science is physics with 62.4% of the students considering it the least interesting of the Sciences and only 8.2%…”
Section: Attitudes Towards Sciencementioning
confidence: 99%
“…The lack of uptake of science in Post-Primary Schools (High-Schools) has been a strong cause for concern both in Ireland (Regan & Childs, 2003) and internationally (Bennett & Hogarth, 2009;Barmby, Kind & Jones, 2008;Hassan, 2008). In publication of the Strategy for Science, Technology and Innovation (2006) Report, the Irish government highlights the need to significantly change the nature of instruction of the Physical Sciences in Post-Primary Schools, in recognition of the continuing decline in numbers taking science subjects through to Senior cycle (16-18 year olds) and beyond to University.…”
Section: Introductionmentioning
confidence: 99%
“…This statement is also possible to find out in the study of Berg (2005). About the significant role of the teacher wrote also Regan & Childs (2003), the teacher have to present the chemical topic in interesting way, it is the main reason according to authors, why pupils like chemistry as a school subject.…”
Section: Discussionmentioning
confidence: 89%